Endolymph movement visualized with light sheet fluorescence microscopy in an acute hydrops model - Brown, Daniel; Pastras, C.; Curthoys, I.; Southwell, C.; Van Roon, L. (2016)
There are a variety of techniques available to investigate endolymph dynamics, primarily seeking to understand the cause of endolymphatic hydrops. Here we have taken the novel approach of injecting, via a glass micropipette, fluorescein isothiocyanate–dextran (FITC-dex) and artificial endolymph into scala media of anaesthetized guinea pigs, with subsequent imaging of the inner ear using Light Sheet Fluorescence Microscopy (LSFM) as a means to obtain highly resolved 3D visualization of fluid movements. Our results demonstrate endolymph movement into the utricle, semicircular canals and endolymphatic duct and sac when more than 2.5 µl of fluid had been injected into scala media, with no apparent movement of fluid into the perilymphatic compartments. There was no movement of endolymph into these compartments when less than 2.5 µl was injected. The remarkable uptake of the FITC-dex into the endolymphatic duct, including an absorption into the periductal channels surrounding the endolymphatic duct, highlights the functional role this structure plays in endolymph volume regulation.